The Secret of Cacklefur Castle - Geronimo Stilton
Enter the world of Geronimo Stilton, where another funny adventure is always right around the corner. Each book is a fast-paced adventure with lively art and a unique format kids 7-10 will love. Moldy mozzarella, it was every mouse's worst nightmare! My old friend Creepella von Cacklefur called me one night and ordered me to join her for the weekend at her family's spooky castle. And before I could say "boo!" she'd mouse-napped me! Now I was stuck in the gloomiest, eeriest castle I'd ever seen. Even worse, I was surrounded by Creepella's creepy family! Oh, would I ever escape back to my safe, cozy mouse hole in New Mouse City?